Political Direction of Anti-Corruption Law in Indonesia: A Legal Policy Analysis of the KPK Law Revision and the New Criminal Code - Asriyani, Arini; Rasyid, Muh. Fadli Faisal; Sarjono, Anastasia (Journal of Law, Politic and Humanities, 2026)
This article analyzes the legal policy evolution of corruption eradication in Indonesia subsequent to the reform of the Corruption Eradication Commission Law and the implementation of Law Number 1 of 2023 about the Criminal Code. Since the reform era, corruption has been regarded as a significant crime managed by a specialized and autonomous institution. Recent legal amendments have altered its institutional standing by incorporating it within the executive branch, creating a supervisory body, and reclassifying people as state civil servants. The new criminal law simultaneously establishes sentencing goals, individualizes punishment, and reclassifies punishments. This research utilizes normative legal analysis using statutory and conceptual methodologies. The results indicate a transition from an exceptional enforcement paradigm to a more cohesive approach within the national legal framework. Although these improvements improve legal systematization and procedural accountability, they also provoke concerns about institutional independence. The efficacy of corruption elimination depends on the state's capacity to harmonize the rule of law, institutional accountability, and enforcement efficacy within a transparent governance framework.